O ensino da produção escrita para alunos iniciantes no aprendizado de língua espanhola: uma pesquisa-ação no curso de Letras - Meniconi, Flávia Colen (2015)
This thesis presents the report, results and findings of an action-research carried out by means of a didactic sequence for the teaching and learning process of argumentative writing in the Spanish language. It took place in the beginner levels of the teaching of this language, in a Language Undergraduate Course at the Language College of the Federal University of Alagoas, in the campus of Maceió. The methodology is qualitative and the study is characterized as action-research, with interventions by the researcher. The author used questionnaires, collection of opinions (filmed and recorded) and field diaries elaborated during the didactic sequence. The written productions of the students, as well as their opinions about the classes/workshops, were the bases for the analysis of the writing process and of the perception of students on such process. The reports in the field diaries and the activities of corrections and rewritings were also important elements of analysis. The author used, as theoretical support, studies on writing as process (BOOKES; GRUNDY, 1988; MADRIGAL ABARCA, 2008; FLOWER; HAYES, 1981; FAYOL, 1991), argumentative theories of rhetorical nature (PERELMAN; OlBRECHTS-TYTECA, 2005; PLANTIN, 2008; REBOUL, 1999; MEYER, 2007), theories on textual genres according to the socio-interactional perspective (MARCUSCHI, 2008) and social-rhetoric studies (BITZER, 1968; BAZERMAN, 2007). The partial findings revealed that the students were capable of producing argumentative texts in the Spanish language, still in the early phases of learning the language. Mistakes related to the progression of ideas, to the use of connectors and linguistic-textual markers, and to the argumentative strategies, were minimized throughout the didactic sequence developed, especially in the phase of explicit teaching. Such factor shows the importance of systematizing the teaching of writing as a process, with didactic sequences directed to textual genres, starting in the very beginning levels of learning the language. The analyses of the collections of the participants’ opinions showed that a vision which is limited to linguistic and lexical aspects of the language, however important, is not enough for the perception related to the sequencing of ideas in the text. Meanwhile, awareness of the importance of organizing ideas in the text, and of the previous planning of arguments, influences the cohesive and coherent writing.